Compound volvulus: An unexpected surgical finding - Laher, Naadiyah (Journal of the Nuffield Department of Surgical Sciences, 2023)
Ileosigmoid knot (ISK) is a rare entity more commonly encountered along the volvulus belt. An important differential is sigmoid volvulus which is amenable to endoscopic reduction where ISK rapidly progresses to gangrenous bowel. A classification system, treatment algorithm and prognostic factors have been determined by the Turkish to assist with management of this rare occurrence. Below we describe a case in an academic hospital in South Africa.